PENGARUH AGEN PERUBAHAN, SALURAN KOMUNIKASI DAN KARAKTERISTIK INOVASI TERHADAP KEPUTUSAN ADOPSI DALAM PELAKSANAAN E-PROCUREMENT DI KABUPATEN SUKOHARJO - Danang Indra Sumardi (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2017)
AbstractThis study aims to (1) know the role of diffusion of innovation variable influence the agent of change, a channel of communication, characteristic of innovation and social condition of the system in the process of diffusion of technology innovation e-procurement in Sukoharjo Regency and (2) know variable diffusion of innovation that a dominant influence in Sukoharjo Regency e-procurement. The result showed that (1) the role of the agent of change has significant impact of the decision adoption/use e-procurement system in Sukoharjo Regency so ii received hypothesis, (2) variable communication have significantimpact of the decision adoption/use e-procirement system in Sukoharjo Regency so hypothesis ii accepted and (3) variable characteristic innovation have significant impact of the decision adoption/use e-procurement significant impact of the decision adption/use e-procurement system in Sukoharjo Regency so hypothesis iii accepted. But the result count the contribution of the percentage of the role of the agent of change, of the use of the communication and characteristic innovation of the decision use e-procurement system in significant influential bidding process, the remaining affected by the outside this research. While the beta coefficient showing influence most dominant of the free on variables bound.Key Words : Diffusion of innovation, e-Procurement AbstrakPenelitian ini bertujuan untuk (1) mengetahui pengaruh variabel difusi inovasi peran agen perubahan, saluran komunikasi, karakteristik inovasi dan kondisi sistem sosial dalam proses difusi teknologi inovasi e-procurement di Kabupaten Sukoharjo dan (2) mengetahui variabel difusi inovasi yang dominan mempengaruhi e-procurement di Kabupaten Sukoharjo. Hasil penelitian menunjukkan bahwa (1) peran agen perubahan memiliki pengaruh yang siginifikan terhadap keputusan adopsi/penggunaan sistem e-proc di Kabupaten Sukoharjo sehingga hipotesis I diterima, (2) variabel saluran komunikasi memiliki pengaruh yang siginifikan terhadap keputusan adopsi/penggunaan sistem e-proc di Kabupaten Sukoharjo sehingga hipotesis II diterima dan (3) variabel karaktersitik inovasi memiliki pengaruh yang siginifikan terhadap keputusan adopsi/penggunaan sistem e-proc di Kabupaten Sukoharjo sehingga hipotesis III diterima. Adapun besaran hasil hitung kontribusi persentase peran agen perubahan, penggunaan saluran komunikasi dan karaktersistik inovasi terhadap keputusan penggunaan sistem E-Proc dalam proses pelelangan signifikan berpengaruh, sedangkan sisanya dipengaruhi oleh variabel di luar penelitian ini. Sedangkan besaran koefisien beta yang menunjukan pengaruh paling dominan dari variabel bebas terhadap variabel terikat.Kata Kunci: Difusi Inovasi, E- Procurement